Mycotic aneurysm detection rates with cerebral angiography in patients with infective endocarditis. (28th April 2014) - Hui, Ferdinand K; Bain, Mark; Obuchowski, Nancy A; Gordon, Steven; Spiotta, Alejandro M; Moskowitz, Shaye; Toth, Gabor; Hussain, Shazam
Abstract : Background: Cerebral angiography remains the gold standard for the detection of mycotic aneurysms, and it has been estimated that ruptured mycotic aneurysms result in 5% of the neurological complications of patients with infective endocarditis (IE). Objective: To determine the diagnostic yield of cerebral angiography in the above patient population and to assess patient factors that might suggest greater or lesser utility. Methods: We retrospectively reviewed 168 patients who underwent cerebral angiography with a diagnosis of IE or infected left ventricular assist device at the Cleveland Clinic between January 2003 and March 2010 in accordance with institutional review board guidelines. Chart and imaging review was performed. Results: 15/168 patients (8.9%) had mycotic aneurysms; 93.3% (14/15) of the patients with mycotic aneurysms presented with CNS hemorrhage and 66.7% (10/15) had acute ischemic findings. Of the 15 patients with mycotic aneurysms on angiography, seven underwent CT angiography and six underwent MR angiography, which showed mycotic aneurysms in three (42.9%) and two cases (one of which was questionable; 33.3%), respectively. Conclusions: Patients with IE or similar sources of central bacterial emboli are prone to neurovascular complications. Approximately 9% of patients with IE at our institution who undergo cerebral angiography have mycotic aneurysms. Presentation with hemorrhage appears to be more predictive of aneurysm, as approximately 22% of patients with IE and hemorrhage were found to have an aneurysm compared with only 1% when hemorrhage was absent. Thus, patients with IE presenting with intracranial hemorrhage should undergo vascular imaging, preferably with cerebral angiography.